Prognostic impact of left ventricular thrombus resolution after myocardial infarction on cardiovascular events and mortality. (25th November 2020) - Hofer, F; Sulzgruber, P; Kazem, N; Horvath, P; Schweitzer, R; Koller, L; Niessner, A
Abstract: Background: Left ventricular thrombus (LVT) is a rare but dreaded complication during the acute phase of acute coronary syndrome (ACS). Incidence rates differ among the observational studies from 1.6% up to 39.0% indicating that many LVT cases might remain undetected. While the prognosis of patients presenting with LVT after ACS has been controversially discussed, it seems intuitive that individuals in whom the thrombus remains have an increased risk for cardiovascular events and mortality. However, profound data on long-term outcome of this highly vulnerable patient population are not available in current literature. Therefore, we aimed to investigate the impact of LVT resolution on patient's outcome from a long-term perspective. Methods: We collected data of patients with acute coronary syndrome (n=2011) who underwent treatment between 01/2016 and 09/2019. Patients with a confirmed LVT were included in this analysis. Repeated echocardiographic data, treatment management and clinical outcomes were collected during follow-up. All-cause mortality and major adverse cardiac events (MACE), defined as nonfatal stroke, nonfatal myocardial infarction, nonfatal systemic embolism and cardiovascular death were chosen as primary and secondary endpoint. Results: Among 2011 patients with ACS, 52 patients (2.6%) developed left ventricular thrombosis (median age: 63±13). 80.5% of LVT patients presented with STEMI. Out of those 52 patients with LVT, 6 died before hospital discharge and 3 did not receive follow-up imaging. In total 13 patients (24%) died. Mean time to thrombus resolution was 23±31 weeks. Mean follow-up time was 98±69.6 weeks. 43 patients received oral anticoagulation including 7 patients (16%) receiving novel oral anticoagulants (NOACs) and 32 patients (84%) Vitamin K antagonists (VKA). All patients developed LVT after anterior wall infarction. From the time of hospital admission all patients were followed prospectively until the primary endpoint was reached. Thrombus resolution was observed in 27 patients (62.8). As expected, thrombus resolution was associated with a significant lower risk of MACE with a crude hazard ratio (HR) of 3.89 (95% CI 1.30–11.65; P=0.015) and mortality with a crude HR of 5.59 (95% CI 1.07–29.07; P=0.041). Notably, the prognostic impact remained stable after comprehensive adjustment for potential confounders with an adjusted HR of 5.38 for MACE and an adjusted HR of 6.10 for overall mortality. Conclusion: Present data clearly highlighted the prognostic potential of thrombus resolution on both MACE and all-cause mortality in individuals presenting with LVT after ACS. Therefore, thrombus resolution might be considered for risk stratification and an intensified anti-thrombotic approach should be taken into account in this highly vulnerable patient population. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Medical University of Vienna